Pengaruh Agresi Militer Belanda terhadap Perkembangan Politik Indonesia Tahun 1947-1949 - Dini Ayu Amalia; Shabrina Arriby Leone; Jauza Alya Yurindhiya; Romadi Romadi; Dimas Anggoro (SOSIAL : Jurnal Ilmiah Pendidikan IPS, 2026)
This study examines the impact of Dutch Military Aggression I (1947) and Dutch Military Aggression II (1948–1949) on the political development of Indonesia during the early years of independence. Employing the historical method (heuristics, source criticism, interpretation, and historiography) and a qualitative diachronic-synchronic approach, the research analyses primary and secondary sources concerning internal political dynamics and the Republic of Indonesia’s international relations in the period 1947–1949. The findings reveal that both Dutch military aggressions paradoxically served as crucial catalysts for the acceleration of national political consolidation and maturation in Indonesia. The First Aggression triggered international condemnation, transformed the Republic’s status from “rebels” to a sovereign state defending its independence, strengthened national solidarity, and gave birth to the integration of armed struggle and diplomacy—the precursor to the Total People’s Defense doctrine. Meanwhile, the Second Aggression, marked by the occupation of Yogyakarta and the arrest of republican leaders, led to the establishment of the Emergency Government of the Republic of Indonesia (PDRI), closer civil-military coordination, unification of political parties and societal organizations, and heightened global pressure that ultimately resulted in the recognition of sovereignty in 1949. Overall, Dutch military pressure expedited the transformation of political structures, bolstered the legitimacy of the Republican government, and secured both de facto and de jure recognition of Indonesian independence.